XVIII Colloquium Spectroscopicum Internationale : plenary lectures presented at the XVIII Colloquium Spectroscopicum International, Grenoble, France, 15-19 September 1975 - Robin, J. P. (Pergamon Press, 1976)
XVIII Colloquium Spectroscopicum Internationale is a collection of plenary lectures presented at the 18th Colloquium Spectrospicum International, held at Grenoble, France on September 15-19, 1975. This book is composed of seven chapters, and begins with the potentials, advantages, and applications of X-ray and Mossbauer spectroscopy. The succeeding chapters deal with the design of fluorometric methods, the general aspects of the classical light sources (arc and spark) and their contributions to the accuracy of spectrochemical results, and the utility of electron microscopy for structure determ.